Motor unit potential induced repetitive discharges (MIRDs): Description of an unusual iterative discharge. Issue 6 (25th October 2013) - So, Noel F.; Rubin, Devon I.; Jones, Lyell K.; Litchy, William J.; Sorenson, Eric J.
ABSTRACT Introduction: Repetitive discharges may be recorded during nerve conduction studies (NCS) or during needle electromyography in a muscle at rest. Repetitive discharges that occur during voluntary activation and are time‐locked to voluntary motor unit potentials (MUP) have not been described. Methods: Retrospective review of motor unit potential induced repetitive discharges (MIRDs) identified in the EMG laboratory. Characteristics of each MIRD, patient demographics, other EMG findings in the same muscle, and electrophysiological diagnosis were analyzed. Results: MIRDs were observed in 15 patients. The morphology and number of spikes and duration of MIRDs varied. The discharges fired at rates of 50–200 Hz. All but 2 patients had EMG findings of a chronic neurogenic disorder. Conclusions: MIRDs are rare iterative discharges time‐locked to a voluntary MUP. The pathophysiology of MIRDs is unclear, but their presence may indicate a chronic neurogenic process. Muscle Nerve48: 977–979, 2013